Mohammed, Seal of the Prophets? - Calverley, Edwin E. (The Muslim world, 1936)
[The following letter and the reply to the question raised by an Ahmadiyya missionary will be of interest to our readers. We welcome discussions that throw light on the real character of Islam–Ed.]